Cistanches Herba: An overview of its chemistry, pharmacology, and pharmacokinetics property. (12th June 2018) - Fu, Zhifei; Fan, Xiang; Wang, Xiaoying; Gao, Xiumei
Abstract: Ethnopharmacological relevance: Cistanches Herba is an Orobanchaceae parasitic plant. As a commonly used Traditional Chinese Medicine (TCM), its traditional functions include treating kidney deficiency, impotence, female infertility and senile constipation. Chemical analysis of Cistanches Herba revealed that phenylethanoid glycosides, iridoids, lignans, oligosaccharides, and polysaccharides were the main constituents. Pharmacological studies demonstrated that Cistanches Herba exhibited neuroprotective, immunomodulatory, hormonal balancing, anti-fatigue, anti-inflammatory, hepatoprotection, anti-oxidative, anti-bacterial, anti-viral, and anti-tumor effects, etc. The aim of this review is to provide updated, comprehensive and categorized information on the phytochemistry, pharmacological research and pharmacokinetics studies of the major constituents of Cistanches Herba. Materials and methods: The literature search was conducted by systematic searching multiple electronic databases including SciFinder, ISI Web of Science, PubMed, Google Scholar and CNKI. Information was also collected from journals, local magazines, books, monographs. Results: To date, more than 100 compounds have been isolated from this genus, include phenylethanoid glycosides, carbohydrates, lignans, iridoids, etc. The crude extracts and isolated compounds have exhibited a wide range of in vitro and in vivo pharmacologic effects, such as neuroprotective, immunomodulatory, anti-inflammatory, hepatoprotection, anti-oxidative, anti-bacterial, and anti-tumor effects. The phenylethanoid glycosides, echinacoside and acteoside have attracted the most attention for their significantly neuropharmacology effects. Pharmacokinetic studies of echinacoside and acteoside also have also been summarized. Conclusion: Phenylethanoid glycosides have demonstrated wide pharmacological actions and have great clinical value if challenges such as poor bioavailability, fast and extensive metabolism are addressed. Apart from phenylethanoid glycosides, other constituents of Cistanches Herba, their pharmacological activities and underlying mechanisms are also need to be studied further. Graphical abstract: fx1